Disrupted Brain Connectivity Networks in Aphasia Revealed by Resting-State fMRI - Chen, Xiaoyun; Chen, Liting; Zheng, Senning; Wang, Hong; Dai, Yanhong; Chen, Zhuoming; Huang, Ruiwang (Frontiers in Aging Neuroscience, 2021)
Aphasia is characterized by disability of spontaneous conversation, listening, understanding, retelling, naming, reading or writing. However, the neural mechanisms of language damage after stroke are still under discussion. This study aimed to investigate the global and nodal characterization of the functional networks in aphasic stroke patients based on resting-state functional magnetic resonance imaging (fMRI). Twenty-four right-handed patients with aphasia after stroke and 19 healthy controls (HC) were underwent a 3-T fMRI scans. Whole-brain large-scale functional connectivity network were then constructed based on Power’s atlas of 264 functional regions of interest, and the global and nodal topological properties of these networks were analyzed using graph theory approaches. The results showed that aphasic patients had decreased in small-worldness (sigma), normalized clustering coefficient (gamma), and local efficiency (Eloc) values. Further, Eloc was positively correlated with language ability, retelling, naming and listening comprehension in aphasic patient. Aphasic patients also had decreased nodal degree and decreased nodal efficiency in the left postcentral gyrus, central opercular cortex, and insular cortex. Our results suggest that the global and local topology attributes were altered by injury in the aphasic stroke patients. We argue that the local efficiency of brain networks might be used as a potential indicator of basic speech function in patients with aphasia.